Maintaining Customer Loyalty Based on Social Media Marketing, Customer Engagement, Lifestyle, and TikTokShop Promotion with Satisfaction as a Mediator - Muhamad Farid Mahmud; Lies Handrijaningsih; Rini Tesniwati; Disna Dwi Fitrika (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Customer satisfaction is a crucial step in the survival and expansion of increasingly competitive companies because it connects many aspects of loyalty. Loyalty is the key to business sustainability, but it is not easy to build, especially in the increasingly competitive and innovative digital era. Objective: The purpose of this study is to examine and analyze how social media marketing, satisfaction, customer engagement, lifestyle, and promotions influence TikTok Shop loyalty. Methods: This study employs a quantitative methodology to evaluate primary data, specifically structural equation modeling. 200 individuals were surveyed using a questionnaire instrument to collect credible data. Purposive sampling was used to collect non-probability data. SmartPLS 4.0 served as a testing tool. Results: According to the study's findings, social media marketing, customer engagement, lifestyle, and promotions all have a direct influence on consumer satisfaction and loyalty. Satisfaction has a significant impact on customer loyalty. Customer satisfaction also serves as a mediator between the four of independent variable that influence loyalty. Conclusion: These findings can be applied as a flywheel marketing technique by TikTok Shop owners.